Langerhans Cells Come in Waves - Romani, Nikolaus (Immunity, 2012)
It is unclear how the Langerhans cell (LC) network is maintained in adult epidermis. In this issue of Immunity, Seré et al. (2012) show that LCs are replenished in two waves. Monocyte-derived, short-lived LCs come first. A second wave follows, and these LCs of nonmonocytic origin are long-lived.